Tasmola Kurgans in Aiyrtas Valley in Central Kazakhstan - Arman Z. Beisenov; Darkhan T. Shashenov (Нижневолжский археологический вестник, 2020)
The report introduces study materials of new kurgans dating back to the early Iron Age of Central Kazakhstan. Monuments are located in the eastern part of the Karaganda region. Geographically, this territory is part of the Kazakh Upland’s eastern region. In three cemeteries located at the area of Mount Aiyrtas, 8 kurgans were excavated. Mounds of 5–13 m in diameter and 0.2–1.2 m tall are built of earth and stone. Eachmound contains one grave. Dead bodies are placed head to the northwest. Despite the fact the kurgans were heavily robbed, the data about the funeral rite demonstrate important aspects of the of the ancient population culture of this region, as well as the found objects do. According to archaeological data, the monuments belong to the Tasmola culture of the Saka tribes time period. The materials obtained indicate that representatives of the ordinary population are buried at the studied sites. Monuments are dating back to VII–V centuries BC. The study of monuments left by the lower class is a poorly researched aspect of tasmol culture’s population, so it is very important. The data accumulated by now have been obtained from burials being widely scattered over a large area. Studying small mounds in places of their accumulation is more promising, though. One of such places is Aiyrtas valley, where large number of small mounds is located, as parts of nearby cemeteries. There are still some unexcavated kurgans in Aiyrtas-2 kurgan cemetery remaining. As it is known, a complete study of burial grounds makes it possible to draw more substantiated conclusions about the social structure of ancient society. There are other burial grounds in the area, including elite kurgans.